A Study on problems and challenges faced by Nagpur farmers with respect to dairy business - Mate, Kundan; Tekade, Atul B. (Journal of Neonatal Surgery, 2025)
The aim of this study is to make comparative study of farmers who are engaged with dairy farming by considering the different policies and factors such as Economic, Marketing , Communicational and Infrastructure problems etc. For this study the sample area selected was Nagpur tahsil. A total no. of 200 dairy farmers were selected and interviewed from the tahsil randomly. The data was collected through personal interview. The Primary data were collected from the farmers of the tahsil through the use of questionnaires and were analyzed using both descriptive and inferential statistics. The study concludes by highlighting the importance of socio-psychological problems of farmers, primary challenges (Economic) in selling milk and related products, communicational problems, technical constraints, marketing constraints and availability of dairy-related infrastructure (e.g., cold storage, transportation) facilities.